AGE DETERMINATION AND PALAEOGEOGRAPHIC RECONSTRUCTION OF DIAPONDIA ISLANDS IN NW GREECE, BASED ON CALCAREOUS NANNOFOSSILS - Makrodimitras, G.; Stoykova, K.; Vakalas, I.; Zelilidis, A. (Bulletin of the Geological Society of Greece, 2010)
Diapondia islands - Ereikoussa, Othonoi and Mathraki – extended in the north-western area of Greece, are part of the external Ionian zone of the Hellenides. The exposed sedimentary succession of the three islands consists of up to 74m thick submarine fans, interpreted as inner fan deposits. The determination of the sediment ages is based on the study of calcareous nannofossils, which came from almost 63 samples covering geological cross sections across the coast line of the three islands. The recorded nannofossil associations are assigned to the biozones of Martini’s (1971) standard scheme. According to the age determination clastic sedimentation in the studied area started during the Late Oligocene and finished during the Early Miocene time. Moreover, the age determination and in accordance with the previous results, indicate that also the Ionian thrust activity started during Late Oligocene.